EVALUASI PENGGUNAAN OBAT ANTI HIPERTENSI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Woro Supadmi (Pharmaciana, 2011)
The intervention led to various complications in dialysis patients include hypertension intradialitik as a result of hemodynamic changes.The phenomenon of the paradox of which caused activation of endogenous vasopresor due to changes in volume status and antihypertensive medication terdialisisnya factor. This study aims to determine patterns of use of antihypertensive drugs, evaluating the rationality and side effects of antihypertensive drugs based on literarur. This study was performed with the patient’s condition based on the observation of patients to see medical records drug data, laboratory data of patients and patient’s condition.Retrospective study of hemodialysis patients in the hospital PKU Muhammadiyah Yogyakarta year period from 2009 to 2010.Patients according to inclusion criteria, anti-hypertensive drug receipts and complete medical record data.Evaluation of rationality involves the use of antihypertensive drugs right dose, right patient and side effects based on the Drug Information Hand Book 2005, Handbook of Clinical Drug Data, 2002. The study found 60 patients who fit the inclusion criteria.Based on the research patterns of use of antihypertensive drugs in patients with hemodialysis is captoril, furosemide, nifedipine, lisinopril, amlodipine, valsatran and clonidin. Evaluation rationality inappropriate use of drugs dose use of captopril 11 patients of 34 patients and furosemide 18 patients from 52 patients, inappropriate use of captopril patients was 9 patients of 34 patients.Side effects that occur in patients with hypokalemia due to the use of furosemide is 40 patients, cough due to captopril was 13 patients, side effects of nifedipine gastrointestinal disorders cough and 11 patients, 5 patients cough lisinopril.Conclusion:he use of antihypertensive medications in hemodialysis patientsat RSU PKU Muhammadiyah Yogyakarta is rational.